Community Preparedness for Earthquakes Based on Settlement Environment Analysis. - Novrikasari Novrikasari; Yuanita Windusari; Misnaniarti Misnaniarti; Ikhsan Ikhsan; Andries Lionardo; Azhar Kholiq Affandi; Henni Febriawati; Pitri Noviadi; Nurrobikha Nurrobikha (Universitas Airlangga, 2022)
Introduction: Bengkulu is located on an active collision zone between two tectonic plates, namely the Eurasian Plate and the Indo-Australian Plate. As the result, earthquakes, floods, landslides, and tidal waves are common in Bengkulu. Sepang Bay is part of Bengkulu Province adjacent to the ocean, making it vulnerable to earthquakes and tsunamis. This study aims to examine the relationship between the residential environment and natural disaster preparedness in Sepang Bay, Bengkulu Regency. Methods: The type of research used is analytical observation with cross-sectional design. Data are collected from interviews, questionnaires, observations, and documentation from a total of 100 respondents selected by proportional random selection from each neighborhood in Sepang Bay Village, based on the proportion of heads of family in each neighborhood. Results and Discussion: When an earthquake occurs, there is a relationship between the residential environment and the community's preparedness. As the existing supporting infrastructure is not properly utilized, people who live in substandard settlements do not have adequate equipment to deal with seismic disasters. When an earthquake occurs, there is a relationship between the settlement environment and the community's preparedness. Because the existing supporting infrastructure is not being used properly, people who live in poor settlements have poor preparedness as well. Conclusion: The Sepang Bay Village Community, Bengkulu, which is located along the Panjang Beach, found a relationship between the settlement environment and earthquake preparedness (p = 0.021, PR 2.127).